Application of serial communication in industrial automation processes - Auccahuasia, Wilver (2021)
In the field of engineering, the most required mechanisms are those in charge of the transfer of information, between the different components of the equipment or system, as well as the exchange of information between the equipment and the different control or management systems is required, that it is required to know the status of the equipment. These requirements are important to be able to measure the performance of the equipment and we need to have the information, one of the protocols that we have available is the serial communication port, through the RS-232 protocol and with the DB9 serial connector and now the USB, in The present work presents a method to exploit this data that we can export through this port as well as the description of an application made in Labview to connect to the equipment by configuring a virtual port "COM3", from which we can receive the information and its subsequent storage and exploitation, the results show that it can be connected with all the equipment that has the serial communication port and by the labView development tool it allows us to connect with different hardware architectures and with greater compatibility with serial communication.